Synergistic interactions of the anti‑casein kinase 2 CIGB‑300 peptide and chemotherapeutic agents in lung and cervical preclinical cancer models - Perera, Yasser (2014)
CIGB‑300 is a novel clinical‑stage synthetic peptide that impairs the casein kinase 2 (CK2)‑mediated phosphorylation of B23/nucleophosmin in different experimental settings and cancer models. As a single agent, CIGB‑300 induces apoptosis in vitro and in vivo and modulates an array of proteins that are mainly involved in drug resistance, cell proliferation and apoptosis, as determined by proteomic analysis. However, the clinical oncology practice and cumulative knowledge on tumor biology suggest that drug combinations are more likely to cope with tumor complexity compared to single agents. in this study, we investigated the antiproliferative effect of CIGB‑300 when combined with different anticancer drugs, such as cisplatin (alkylating), paclitaxel (antimitotic), doxorubicin (antitopoisomerase II) or 5‑fluorouracil (DNA/RNA antimetabolite) in cell lines derived from lung and cervical cancer. Of note, using a Latin square design and subsequent analysis by Calcusyn software, we observed that paclitaxel and cisplatin exhibited the best synergistic/additive profile when combined with CIGB‑300, according to the combination and dose reduction indices. Such therapeutically favorable profiles may be explained by a direct cytotoxic effect and also by the observed cell cycle impairment following incubation of tumor cells with selected drug combinations. Importantly, on in vivo dose‑finding schedules in human cervical tumors xenografted in nude mice, we observed that concomitant administration of CIGB‑300 and cisplatin increased mice survival compared to single‑agent treatment. Collectively, these findings provide a rationale for combining the anti‑CK2 CIGB‑300 peptide with currently available anticancer agents in the clinical setting and indicate platins and taxanes as compounds with major perspectives.